Pengaruh Penggunaan Media Pembelajaran Visual Powerpoint Terhadap Peningkatan Hasil Belajar Pendidikan Agama Kristen Siswa Kelas IX SMP Negeri 2 Nainggolan Tahun Pembelajaran 2023/2024 - Michael Sihite; Dorlan Naibaho; Marudut Situmorang; Sabar Rudi Sitompul; Taripar Aripin Samosir (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The purpose of this research is to determine whether there is an improvement in the learning outcomes of Christian Religious Education and Character Education for students who are taught using visual PowerPoint learning media compared to those taught without visual PowerPoint learning media in class IX at SMP Negeri 2 Nainggolan for the academic year 2023/2024. This research employed an experimental method, specifically the Posttest-Only Control design. The population consisted of all ninth-grade students at SMP Negeri 2 Nainggolan who were Protestant Christians for the academic year 2023/2024, totaling 85 students. The sample was selected using purposive sampling, with the condition that the experimental learning material was taught in these classes. Class IX-1, with 30 students, was designated as the experimental group, while class IX-2, also with 30 students, served as the control group. The research instrument comprised a 40-item test. The t-test used was the Separated Variance t-test, in accordance with the analysis requirements, where n1 = n2, and the variances of both sample groups were homogenous. The results of the hypothesis testing showed that the calculated t-value was 16.39, which was greater than the critical t-value (α = 0.05; df = n1 + n2 - 2 = 58) = 1.671. Therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. This research concludes that the learning outcomes of Christian Religious Education and Character Education for students who were taught using visual PowerPoint learning media are higher than those taught without visual PowerPoint learning media in class IX at SMP Negeri 2 Nainggolan for the academic year 2023/2024.